2006
DOI: 10.1007/s00134-006-0428-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vaporized perfluorohexane and partial liquid ventilation on regional distribution of alveolar damage in experimental lung injury

Abstract: PFH was associated with a more homogeneous attenuation of alveolar damage across the lungs, although this therapy had more pronounced effects in nondependent zones. PLV showed the opposite pattern, with more important reduction in alveolar damage in dependent lung regions. Interestingly, reduction in alveolar damage with PFH was as effective as with PLV in dependent zones. Our findings suggest that vaporized perfluorocarbon could be advantageous as adjunctive therapy in the treatment of acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…In any case, if the PFC vapor remains in the circuit, it could somehow contribute to the aerosol therapy, as beneficial effects of vaporized PFCs on lung function have previously been described in various animal models of lung injury. (25)(26)(27) The surfactant recovery rates for IC-1.23 and IC-1.4 were higher than those observed for the PFCs. In the case of IC-1.1 a leak of surfactant was detected between the aerosol chamber and the proximal tip of the inhalation catheter, explaining the high surfactant loss in this particular case.…”
Section: Aerosolization Rate Emission Rate and Pfc And Surfactant Lcontrasting
confidence: 71%
“…In any case, if the PFC vapor remains in the circuit, it could somehow contribute to the aerosol therapy, as beneficial effects of vaporized PFCs on lung function have previously been described in various animal models of lung injury. (25)(26)(27) The surfactant recovery rates for IC-1.23 and IC-1.4 were higher than those observed for the PFCs. In the case of IC-1.1 a leak of surfactant was detected between the aerosol chamber and the proximal tip of the inhalation catheter, explaining the high surfactant loss in this particular case.…”
Section: Aerosolization Rate Emission Rate and Pfc And Surfactant Lcontrasting
confidence: 71%
“…Diffuse alveolar damage was quantified using a weighted scoring system, as previously described (19). Messenger RNA expression of interleukin (IL)-1, IL-6, IL-8, tumor necrosis factor (TNF)-α, transforming growth factor-β, amphiregulin, and tenascin-c was analyzed in lung tissue using quantitative real-time polymerase chain reaction.…”
Section: Postmortemsmentioning
confidence: 99%
“…Recently published data by Gama de Abreu and Spieth suggest that PFH vapor may similarly lead to an attenuation of alveolar damage and preservation of lung ultrastructure [12,13]. Future possible indications for the use of PFH vapor could therefore lie in the prophylaxis or in the early treatment of acute lung injury making use of its protective and antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 92%
“…In vivo studies with inhaled PFC documented a reduction in alveolar edema, vascular leakage, and inflammatory response [11][12][13]. In vitro studies using liquid PFC indicated further antiinflammatory effects in alveolar macrophages [14] with a decrease in reactive oxygen species [15] and suggested that PFC may protect lung epithelial cells from neutrophil-mediated injury [16].…”
mentioning
confidence: 96%